Service-learning far from home. Volunteering experience in Nicaragua - Cimadomo, Guido (My University, 2023)
The volunteer project is conceived as a service-learning experience for students of the University of Malaga, who collaborate in the activities of the planning office of the municipality of Bonanza. Architecture is not the only discipline involved, an interdisciplinary approach is sought (with profiles from Tourism, Social Work), to enrich the experiences of the volunteers and the results produced. The interventions to be carried out are agreed annually with the counterpart, aimed at improving the conditions of the local population (SDG 11). Indirectly, the local institution is also strengthened (SDG 16). The activities, which include museum and sports project design, population surveys, training and strengthening of local initiatives related to health, or the diagnosis of one of the conflictive neighborhoods of the municipality, respond to sustainability over time, coherence with the criteria and guidelines of the Andalusian Agency of International Cooperation for Development (AACID) volunteer and cooperation activities, gender and equal opportunity issues. The experience, which involves immersion in a cultural context far from the students’ habits, not only offers a work experience for the students that can open new perspectives for the future, but also generates personal growth that would be difficult to achieve in other types of academic activities. The fact that the activity is not linked to official academic programs brings students with real interests to be involved in the improvement of the social fabric through their knowledge and dedication. At the same time, activities are carried out to bring students closer to research, delving deeper into traditional Mayangna housing, the water cycle in a Mayangna village, and climate change effects on a society deeply rooted with nature. Among the achieved results, master theses, book chapters and presentations at international conferences.
Keywords: Aprendizaje por experiencia; Pedagogía crítica; Voluntariado; Service-Learning; Creditless programs; Nicaragua; Volunteering; Cooperation